Nociceptin/orphanin FQ (N/OFQ) modulates immunopathology and airway hyperresponsiveness representing a novel target for the treatment of asthma. (6th March 2016) - Singh, Shailendra R; Sullo, Nikol; Matteis, Maria; Spaziano, Giuseppe; McDonald, John; Saunders, Ruth; Woodman, Lucy; Urbanek, Konrad; De Angelis, Antonella; De Palma, Raffaele; Berair, Rachid; Pancholi, Mitesh; et al.
Abstract : Background and Purpose: There is evidence supporting a role for the nociceptin/orphanin FQ (N/OFQ; NOP) receptor and its endogenous ligand N/OFQ in the modulation of neurogenic inflammation, airway tone and calibre. We hypothesized that NOP receptor activation has beneficial effects upon asthma immunopathology and airway hyperresponsiveness. Therefore, the expression and function of N/OFQ and the NOP receptor were examined in healthy and asthmatic human airway tissues. The concept was further addressed in an animal model of allergic asthma. Experimental Approach: NOP receptor expression was investigated by quantitative real‐time PCR. Sputum N/OFQ was determined by RIA. N/OFQ function was tested using several assays including proliferation, migration, collagen gel contraction and wound healing. The effects of N/OFQ administration in vivo were studied in ovalbumin (OVA)‐sensitized and challenged mice. Key Results: NOP receptors were expressed on a wide range of human and mouse immune and airway cells. Eosinophils expressed N/OFQ‐precursor mRNA and their number correlated with N/OFQ concentration. N/OFQ was found in human sputum and increased in asthma. Additionally, in asthmatic human lungs N/OFQ immunoreactivity was elevated. NOP receptor activation inhibited migration of immunocytes and increased wound healing in airway structural cells. Furthermore, N/OFQ relaxed spasmogen‐stimulated gel contraction. Remarkably, these findings were mirrored in OVA‐mice where N/OFQ treatment before or during sensitization substantially reduced airway constriction and immunocyte trafficking to the lung, in particular eosinophils. N/OFQ also reduced inflammatory mediators and mucin production. Conclusions and Implications: We demonstrated a novel dual airway immunomodulator/bronchodilator role for N/OFQ and suggest targeting this system as an innovative treatment for asthma.